2017
DOI: 10.1177/0267659117728195
|View full text |Cite
|
Sign up to set email alerts
|

Shed-blood-separation and cell-saver: an integral Part of MiECC? Shed-blood-separation and its influence on the perioperative inflammatory response during coronary revascularization with minimal invasive extracorporeal circulation systems – a randomized controlled trial

Abstract: The use of a cell-saver and the processing of shed blood as an integral part of MiECC significantly reduces the systemic cytokine load. We, therefore, recommend the integration of cell-saving devices in MiECC to reduce the perioperative inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
0
18
0
9
Order By: Relevance
“…As Fig. illustrates, the earlier studies show a beneficial effect while the recent studies show no effect with a statistically significant difference in the effect size between the two groups. This explains the observed heterogeneity.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…As Fig. illustrates, the earlier studies show a beneficial effect while the recent studies show no effect with a statistically significant difference in the effect size between the two groups. This explains the observed heterogeneity.…”
Section: Discussionmentioning
confidence: 77%
“…reported mean transfusion volumes and did not report the proportions of patients who received blood transfusion in the CS and non‐CS groups; therefore, it was not included. Fifteen studies were included in the final analysis; of which, all reported RBC transfusion rate, and eleven reported platelet and FFP transfusion rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] Other equipment for immune response in cardiac surgery are minimal invasive extracorporeal circulation and the cell-saver both of which may have favorable effects on the immune response, reducing the systemic cytokine load. [31] All these measures affecting the immune response and inflammation may be reasonable and should be kept in mind for COVID-19 patients during cardiac surgery.…”
Section: And Further Potential Effects Of Cardiac Surgerymentioning
confidence: 99%